Economic recovery of the new poor created by COVID-19: Evidence from Bangladesh - Gomes, Mohima; Jahan, Nusrat; Shatil, Tanvir; Tahsin, Nabila; Das, Narayan; Matin, Imran (Taylor and Francis, 2024)
This article was published in The Development in Practice [©2024 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/09614524.2023.2267795 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2023.2267795